EV Charging Profiles and Waveforms Dataset (EV-CPW) and Associated Power Quality Analysis - Isla Ziyat; Alia Gola; Patrick R. Palmer; Stephen Makonin; Fred Popowich (IEEE Access, 2023)
The rapid growth of electric vehicle (EV) charging will present challenges to electrical distribution networks and will affect grid operation and reliability. In order to improve the understanding of EV charging behaviour, we present the open access EV Charging Profiles and Waveforms (EV-CPW) dataset for AC charging. The dataset comprises of charging profiles and high-resolution current/voltage AC waveforms for 12 different EV’s, including popular battery EV’s and plug-in hybrid EV’s. A power quality analysis is carried out to compare the EV charging behaviours to new standards recommendations proposed by standards agencies. This includes evaluating power factor, current and voltage distortion, harmonic content and load behaviour in relation to grid voltage and frequency. The preliminary data analysis presented reveals that each EV has distinctive charging characteristics and the power quality analysis indicates variation in the on-board charger circuits employed by the EV’s. The EV-CPW dataset can be used for many more applications and studies, including EV charging infrastructure planning, demand management, EV charging coupled with renewable energy studies, power quality analysis, equipment lifetime studies and power electronics design. The dataset can be accessed at https://doi.org/10.7910/DVN/F81CXW.